2020
DOI: 10.2478/aucft-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Properties of Sakada Produced from Blends of Cassava and African Yam Bean Flours

Abstract: This study investigated the effect of African yam bean flour (AYF) inclusion on the quality of sakada. Fermented cassava mash (FCM) and AYF were blended at ratios (% w/w) 100:0 (control), 90:10, 80:20, 70:30, and 60:40. Sakada was produced using the blends, and its nutritional and sensory properties were determined. Protein, fat, crude fibre, P, Ca, phytate, and oxalate contents of sakada increased (p < 0.05) with increasing AYF level, while moisture, carbohydrate, and cyanide decreased. The incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These studies showed possibilities of partial substitution for improved products like buns, meat pies, sausage rolls, cakes, biscuits, doughnuts, and chin–chin. Despite this research and others supporting the use of cassava as composite flour for substitution of wheat, limited studies have been reported on the improvement of the nutritional quality of cassava–wheat composite flour (Ajayi et al, 2020). Consumption of products from nonenriched cassava–wheat flour may put the health of consumers at risk of malnutrition when consumed in relatively high quantities and for a longer period of time.…”
Section: Introductionmentioning
confidence: 93%
“…These studies showed possibilities of partial substitution for improved products like buns, meat pies, sausage rolls, cakes, biscuits, doughnuts, and chin–chin. Despite this research and others supporting the use of cassava as composite flour for substitution of wheat, limited studies have been reported on the improvement of the nutritional quality of cassava–wheat composite flour (Ajayi et al, 2020). Consumption of products from nonenriched cassava–wheat flour may put the health of consumers at risk of malnutrition when consumed in relatively high quantities and for a longer period of time.…”
Section: Introductionmentioning
confidence: 93%
“…African yam bean is grown for its edible seeds and the seed varies in shape and size. African Yam Bean is an herbaceous leguminous plant occurring throughout tropical Africa (Ajayi, Arueya, Adedeji, & Akinlabi, 2020;Izuchukwu, Momoh, & Iorliam, 2019). It is grown as a minor crop in association with yam and cassava.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific findings have shown that cereal gruels are the common complementary foods in developing countries, which is characterized by low energy and protein density due to large volume of water relative to its solid matter contents during preparation (Oludumila & Enujiugha, 2017). Recent studies have shown an improvement in the nutritional compositions of some staple foods following the incorporation of African yam bean which contains 21.78% protein, 220.95 mg/100g Ca, 152 mg/100g K, 33.28 mg/100g P, and 3.75 mg/100g Zn (Ajayi et al, 2020). In Nigeria, African yam bean is a valuable source of plant protein in some localities and are cultivated as a pulse for human consumption.…”
Section: Introductionmentioning
confidence: 99%